68Ga–Prostate-Specific Membrane Antigen Uptake in Dissecting Abdominal Aortic Aneurysm. (June 2020) - Wong, Veronica Chi Ken; Yip, Joshua Wei Liang; Stevanovic, Amanda; Le, Ken; Mansberg, Robert
Abstract : Abstract: An 81-year-old man with prostate adenocarcinoma (Gleason 4 + 3 = 7) treated with brachytherapy and intermittent androgen deprivation therapy was referred for serial 68 Ga–prostate-specific membrane antigen (PSMA-HBED-CC) PET/CT scans for rising prostate-specific antigen. Findings were suggestive of local prostatic recurrence and nodal metastases. An incidental PSMA-avid focus was noted in the anterior wall of an infrarenal aortic aneurysm, with a contrast-enhanced hyperdense region surrounded by a semilunar hypodense region anteriorly, consistent with enlarging dissecting thrombus. Increased PSMA avidity in atherosclerotic hypertensive lesions may relate to active plaque instability, indicating a need for further evaluation.